Printed Strain Sensors for On‐Skin Electronics. Issue 2 (29th November 2021) - Li, Yizong; Liu, Yuxuan; Bhuiyan, Shah Rifat Alam; Zhu, Yong; Yao, Shanshan
Abstract : On‐skin electronics have drawn extensive attention as they revolutionize many aspects of healthcare, motion tracking, rehabilitation, robotics, human–machine interaction, among others. Flexible and stretchable strain sensors represent one of the most explored devices for on‐skin electronics. Many printing techniques have recently emerged showing great promises for manufacturing strain sensors. Herein, it is aimed to provide a timely survey of recent advancements in printed strain sensors for on‐skin electronics. This review starts with an overview of sensing mechanisms for printed strain sensors, followed by a review of various printing techniques employed in fabricating these sensors. The materials, structures, and printing processes of representative strain sensors are discussed in detail for each printing method. Finally, potential applications of printed flexible and stretchable strain sensors are presented focusing on three areas: healthcare, sports performance monitoring, and human–machine interfaces. The review concludes with a discussion of challenges and opportunities for future research. Abstract : Herein, recent progress in printed flexible and stretchable strain sensors for on‐skin electronics is reviewed. This review starts with an overview of strain sensing mechanisms, followed by a summary of various printing methods for fabricating strain sensors. Finally, the applications for on‐skin electronics are presented, focusing on healthcare, sports performance monitoring, and human–machine interfaces.